Kecenderungan dan Perubahan Hujan Ekstrem Harian di Pulau Madura - Ahmad Nur Akma Juangga Fura; Retno Utami Agung Wiyono; Indarto Indarto (Jurnal Ilmu Lingkungan, 2020)
Madura is prone to high level of flood hazard. One of the main causes of floods is the extreme rainfall. Global warming allows changes in the amount of extreme rainfall. This research was conducted to identify and analyze trends, changes, and randomness of the maximum period of 24-hour extreme rainfall data on Madura Island. The method used was a non-parametric method which includes the Median Crossing test, the Mann-Kendall test, and the Rank-Sum test at the significance level of α =0.05. There were 31 rain gauge stations that were selected out of 66 rain gauge stations which has 20 consecutive years period rainfall data. The period of rainfall observation data was between 1991-2015. The highest extreme daily rainfall data was observed at Ketapang station (430 mm) while the lowest extreme daily rainfall data was observed at Saronggi Station (25 mm). It was found that the west side of  Madura Island and the mountain area show higher value of extreme daily rainfall than other area. High intensity of rainfall (> 100 mm) was occurred in Arosbaya, Ketapang and Ambunten stations while other three stations showed lower intensity of rainfall (Tragah, Larangan and Saronggi). The results of the analysis showed that based on the Median Crossing test, most rain stations have data originating from random processes. A small part of the rain stations was analyzed based on the Mann-Kendal test and the Rank-Sum test. The result showed that the maximum 24-hour extreme rain trend was significantly decreased in a few locations  (Kamal, Ketapang, dan Ganding), while most stations (26 stations) have no experience a significant trend.